Trends in energy and macronutrient intake among Taiwanese older adults in 1999-2000, 2005-2008 and 2013-2016 periods - Chih-Hsueh Lin; Hsing-Yi Chang; Tsai-Chung Li; Chiu-Shong Liu; Wen-Yuan Lin; Meng-Chih Lee; Li-Na Liao; Chia-Ing Li; Chih-Yi Hsiao; Hsin-Ling Fang; Wen-Tzu Wu; Cheng-Chieh Lin (BMC, 2023)
Abstract Background This study aimed to explore trends, in 3 periods, in the intake of energy and macronutrients among Taiwanese older adults. Methods Study subjects were those aged ≥65 years in the Nutrition and Health Survey in Taiwan 1999-2000 as well as the surveys in 2005-2008 and 2013-2016. Twenty-four-hour dietary recall data were obtained. This study used the 3 nutrition survey datasets for 1999-2000, 2005-2008, and 2013-2016, including data on the questionnaire, physical examination, and dietary intakes. Each nutrition survey involved the face-to-face household interview, and individual's dietary intake of carbohydrate, fat, and protein (% of energy) was estimated. Subsequently, intake statuses of the three macronutrients were classified into below, meeting, and above intake categories. Results In the 2013-2016 survey, approximately 40% of the older adults had a low intake of energy. The prevalence of older adults with a meeting intake of carbohydrate, fat, and protein have increased from the 1999-2000 to 2013-2016 periods. The prevalence of people having a low intake of carbohydrate declined from the 1999-2000 period to the 2013-2016 period. The prevalence of high fat intake in 2013-2016 was approximately 5% higher than that in 1999-2000. In the 2013-2016 period, the prevalence of low intake of carbohydrate, fat, and protein were 25.9, 24.5, and 4.9%, respectively; moreover, the prevalence of high intake of the aforementioned macronutrients were 38.7, 36.2, and 17.6%, respectively. Conclusions Our study provides important evidence on the dietary patterns, as well as their changes over time among Taiwanese older adults. Such information would be useful for health policy makers about the burden of unbalanced diet and for nutrition educators on planning nutrition promotion interventions about well-balanced dietary for the older persons.